A SHEA BUTTER RICH IN TOCOPHEROLS (VITAMIN E) AT THE DOGON PLATEAU AND SENO BANKASS IN MALI (WEST AFRICA) - Kelly, Bokary Allaye; Davrieux, Fabrice; Bouvet, Jean-Marc (Journal of Phytology, 2018)
Vitellaria paradoxa, a forest tree species plays an important role for rural populations in Mali. The kernel is rich in fat, fatty acids and tocopherols and the butter extrated from the kernel is used in many African kitchens, in pharmacology, cosmetics, local traditional medicine and as Chocolate Butter Equivalent (CBE) in chocolate industry. A consortium funded by the Europena Union has worked on several aspects of shea tree including chemical characterisation of shea butter. In Mali, one of the project partners, five sites were selected, fruits were collected from selected shea trees and sent to Montpellier for chemical analyses assessing among other variables the tocopherol content of the shea butter using liquid chromatography (HPLC). Results of this study shown that shea butter from the Dogon Plateau and the Seno Bankass is richer in tocopherols (Vitamin E) compared to other study sites. Sites were found significantly different for tocopherols content all together as well as for each type of tocopherol. The richness of shea butter from the Dogon Plateau and the Seno Bankass in tocopherols confers to it an important nutritional value for the good healf of rural populations of this zone, shea butter being the main source of fat for cooking in this area.